Changes in lung aeration and respiratory function after open abdominal surgery: A quantitative magnetic resonance imaging study. Issue 8 (29th July 2022) - Ball, Lorenzo; Serafini, Simon Corrado; Braune, Anja; Güldner, Andreas; Bluth, Thomas; Spieth, Peter; Huhle, Robert; Scharffenberg, Martin; Wittenstein, Jakob; Uhlig, Christopher; Robba, Chiara; Schultz, Marcus J.; et al.
Abstract: Background: Atelectasis is one of the most common respiratory complications in patients undergoing open abdominal surgery. Peripheral oxygen saturation (SpO2 ) and forced vital capacity (FVC) are bedside indicators of postoperative respiratory dysfunction. The aim of this study was to describe the changes in lung aeration, using quantitative analysis of magnetic resonance imaging (MRI) and the diagnostic accuracy of SpO2 and FVC to detect postoperative atelectasis. Methods: Post‐hoc analysis of a randomized trial conducted at a University Hospital in Dresden, Germany. Patients undergoing pre‐ and postoperative lung MRI were included. MRI signal intensity was analyzed quantitatively to define poorly and nonaerated lung compartments. Postoperative atelectasis was defined as nonaerated lung volume above 2% of the total lung volume in the respective MRI investigation. Results: This study included 45 patients, 27 with and 18 patients without postoperative atelectasis. Patients with atelectasis had higher body mass index ( p  = .024), had more preoperative poorly aerated lung volume ( p  = .049), a lower preoperative SpO2 ( p  = .009), and a lower preoperative FVC ( p  = .029). The amount of atelectasis correlated with preoperative SpO2 (Spearman's ρ  = −.51, p  < .001) and postoperative SpO2 ( ρ  = −.60, p  < .001), and with preoperative FVC ( ρ  = −.29, p  = .047) and postoperative FVC ( ρ  = −.40, p  = .006). A postoperative SpO2  ≤ 94% had 74% sensitivity and 78% specificity to detect atelectasis, while postoperative FVC ≤ 50% had 56% sensitivity and 100% specificity to detect atelectasis. Conclusion: SpO2 and FVC correlated with the amount of postoperative non‐aerated lung volume, showing acceptable diagnostic accuracy in bedside detection of postoperative atelectasis.